Efektivitas Pembelajaran Fisika Menggunakan Modul Sains Berbasis Local wisdom pada pembahasan Suhu dan Kalor - Choirul Huda; Dyah Siswoningsih; Duwi Nuvitalia (Jurnal Penelitian Pembelajaran Fisika, 2020)
This study aims to determine the effectiveness of local wisdom-based Science learning modules on the subject of temperature and heat in MTs Al-Hadi . The research method used in this study is Quasi Experimental Design. Data processing and analysis using t-test with the help of SPSS. The results of student pretest scores above KKM are 40% of the total 30 students, while 93.3% of students score above KKM at posttest. Thus, the science module based on local wisdom is effective in improving the learning outcomes of SMP/MTs students in the discussion of temperature and heat. The gain test results are 0.63 (moderate) and the significant value of paired-sample t-test is 0,000 <0.05. It can be concluded that learning physics using science modules based on local wisdom is effectively used to improve student learning outcomes.